An Integration of Project-based Learning and Haptic Senses: A Case Study in Architectural Education - Koompong Noobanjong; Benjawan Ubonsri (My University, 2022)
This research examines a mixed pedagogical approach that improves students’ learning capabilities in multidimensions, ranging from architectural knowledge and skills, collaborative ability, to communication proficiency with foreign peers. Based on their own initiatives and interests, students utilized their haptic senses--the characterization of formal and spatial perceptions obtained through bodily movements, touches, and other sensibilities--to develop and explore the selected objects and subjects of inquiries on architecture of central and northern Thailand via workshops and field trips, which become a basis for this study. Being an integration of a project-based and haptic way of learning, the upcoming investigations look into several phases of scholarly activities, including selections of the applicants, topic proposals, analyses and syntheses of case studies, presentations, as well as exhibition of students’ works. As for its methodological tools for data collection and interpretation, the research employs a combined quantitative and qualitative means--e.g., evaluative and observatory worksheets coupled with satisfactory questionnaires--to assess the academic performance, architectural skills, behavioral parameters of the participants, providing a ground to argue that: 1) the students had gained a higher body of knowledge and architectural skills via their haptic experiences with the built environment; and 2) such a project based-learning (PBL) had contributed to substantial improvements on the academic performance of the students.
Keywords: Authentic Learning; Design Education and Practice